Regulation of a Trehalose-Specific Facilitated Transporter (TRET) by Insulin and Adipokinetic Hormone in Rhodnius prolixus, a Vector of Chagas Disease - Leyria, Jimena; El-Mawed, Hanine; Orchard, Ian; Lange, Angela B. (Frontiers in Physiology, 2021)
Using the blood-sucking kissing bug, Rhodnius prolixus as an experimental model, we have studied the involvement of insulin-like peptides (ILPs) and adipokinetic hormone (AKH) signaling in carbohydrate metabolism, focusing on the regulation of the trehalose-specific facilitated transporter (Rhopr-TRET), particularly in the ovaries. We find that trehalose stores in ovaries increase after feeding, synchronously with the beginning of vitellogenesis, but that the transcript expression of enzymes involved in trehalose synthesis show no changes between unfed and blood-fed animals. However, an 8-fold increase in Rhopr-TRET transcript expression is observed in the ovaries post-blood meal. In vivo and ex vivo assays using exogenous insulins and Rhopr-AKH, reveal that Rhopr-TRET is up-regulated in ovaries by both peptide families. In accordance with these results, when ILP and AKH signaling cascades are impaired using RNA interference, Rhopr-TRET transcript is down-regulated. In addition, trehalose injection induces an up-regulation of Rhopr-TRET transcript expression and suggests an activation of insulin signaling. Overall, the results support the hypothesis of a direct trehalose uptake by ovaries from the hemolymph through Rhopr-TRET, regulated by ILP and/or AKH. We also show that Rhopr-TRET may work cooperatively with AKH signaling to support the release of trehalose from the ovaries into the hemolymph during the unfed (starved) condition. In conclusion, the results indicate that in females of R. prolixus, trehalose metabolism and its hormonal regulation by ILP and AKH play critical roles in adapting to different nutritional conditions and physiological states.